Improving the network management of integrated primary mental healthcare for older people in a rural Australian region: protocol for a mixed methods case study. Issue 9 (16th September 2014) - Fuller, Jeffrey; Oster, Candice; Dawson, Suzanne; O'Kane, Deb; Lawn, Sharon; Henderson, Julie; Gerace, Adam; Reed, Richard; Nosworthy, Ann; Galley, Philip; McPhail, Ruth; Cochrane, Eimear Muir
Abstract : Introduction: An integrated approach to the mental healthcare of older people is advocated across health, aged care and social care sectors. It is not clear, however, how the management of integrated servicing should occur, although interorganisational relations theory suggests a reflective network approach using evaluation feedback. This research will test a network management approach to help regional primary healthcare organisations improve mental health service integration. Methods and analysis: This mixed methods case study in rural South Australia will test facilitated reflection within a network of health and social care services to determine if this leads to improved integration. Engagement of services will occur through a governance group and a series of three 1-day service stakeholder workshops. Facilitated reflection and evaluation feedback will use information from a review of health sector and local operational policies, a network survey about current service links, gaps and enablers and interviews with older people and their carers about their help seeking journeys. Quantitative and qualitative analysis will describe the policy enablers and explore the current and ideal links between services. The facilitated reflection will be developed to maximise engagement of senior management in the governance group and the service staff at the operational level in the workshops. Benefit will be assessed through indicators of improved service coordination, collective ownership of service problems, strengthened partnerships, agreed local protocols and the use of feedback for accountability. Ethics, benefits and dissemination: Ethics approval will deal with the sensitivities of organisational network research where data anonymity is not preserved. The benefit will be the tested utility of a facilitated reflective process for a network of health and social care services to manage linked primary mental healthcare for older people in a rural region. Dissemination will make use of the sectoral networks of the governance group.